Symbolic Adoption of Livestock Based Technologies After Termination of NAIP - K.L.Dangi and Ramesh Kumar Damor, (Indian Journal of Extension Education, 2013)
The National Agricultural Innovation Project (NAIP) was launched in the country during 2006. It has been focusing oninnovations in agricultural technology. The objective was to address the poverty elevation and creating income generationavenues for disadvantaged people leading to livelihood and nutritional security. The consortium project worth ` 18.3 crorewas given to MPUAT Udaipur, Rajasthan. Process evaluation of livestock based IFS interventions in terms of symbolicadoption behavior of tribals about Livestock based IFS was carried out in Dungarpur District of Rajasthan, India. Total104 beneficiaries were interrogated and respondents were categorized into three groups of future possibilities of adoptionlevel along with ranking of sub- interventions to be adopted in livestock. The results indicated that majority 95.19 per centof tribals expressed moderate certainty for future adoption of livestock based IFS interventions followed by 4.81per centof them reporting high certainty of future adoption of IFS interventions even after the termination of the project. Norespondent was found under low certainty of adoption. Further, Improved farm implements, Artificial Insemination,Green fodder production, feeding pattern, Nirbhik breed of poultry, processing equipments and selling of products at thecollection centers were the sub- aspects of Livestock based IFS for which the NAIP beneficiaries were certain forcontinuing the adoption after closing of the project. The results are encouraging and reflecting the positive impact of NAIPon tribal beneficiaries in Dungarpur district of Rajasthan state. Based on the findings, it is recommended that the NAIPforlivestock based IFS must be replicated elsewhere with the same interventions and the beneficiaries of the area besupported for sustaining the advocated interventions after its termination.